Network Capital and Internationalization: Evidence from Chinese High-Tech SMEs - Hang Ju; Shamsul Huda Abd Rani; Mohamad Hanif Abu Hassan (Journal of Frontier in Economic and Management Research, 2025)
This study examines the mediating role of innovation strategy in the relationship between network capital and the internationalization of Chinese high-tech small and medium-sized enterprises (SMEs), as well as the moderating effect of government policy on this mediating pathway. Based on survey data collected from 289 high-tech SMEs located in Shenzhen, China, a moderated mediation model was tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that innovation strategy serves as a significant mechanism through which network capital enhances international performance. Furthermore, government support plays a critical moderating role by strengthening the indirect effect of network capital on internationalization via innovation strategy. Specifically, the mediating effect is more pronounced under high levels of government policy support. These findings contribute to the literature on internationalization by elucidating a conditional process model that explains how relational resources are transformed into global competitive advantage through strategic innovation, contingent on institutional support. The study offers practical implications for SME managers seeking to leverage external networks and innovation capabilities, as well as for policymakers aiming to design effective public interventions that facilitate international expansion.